The 2015 International Society for the Study of Vulvovaginal Disease (ISSVD) Terminology of Vulvar Squamous Intraepithelial Lesions. Issue 2 (February 2016) - Bornstein, Jacob; Bogliatto, Fabrizio; Haefner, Hope K.; Stockdale, Colleen K.; Preti, Mario; Bohl, Tanja G.; Reutter, Jason
Abstract : OBJECTIVES: The impact of terminology for vulvar intraepithelial lesions has been significant over the years, because it has affected diagnosis, treatment, and research. The introduction of the Lower Anogenital Squamous Terminology (LAST) in 2012 raised 2 concerns in relation to vulvar lesions: firstly, the absence of reference to "differentiated vulvar intraepithelial neoplasia" (differentiated VIN) could lead to its being overlooked by health care providers, despite its malignant potential. Secondly, including the term "low-grade squamous intraepithelial lesion" (LSIL) in LAST recreated the potential for overdiagnosis and overtreatment for benign, self-limiting lesions. MATERIALS AND METHODS: The International Society for the Study of Vulvovaginal Disease (ISSVD) assigned the terminology committee the task of developing a terminology to take these issues into consideration. The committee reviewed the development of terminology for vulvar SILs with the previous 2 concerns in mind and reviewed several new terminology options. RESULTS: The final version accepted by the ISSVD contains the following: 1) Low-grade SIL of the vulva or vulvar LSIL, encompassing flat condyloma or human papillomavirus effect. 2) High-grade SIL or vulvar HSIL (which was termed "vulvar intraepithelial neoplasia usual type" in the 2004 ISSVD terminology). 3) Vulvar intraepithelial neoplasia, differentiated type. CONCLUSION: The advantage of the new terminology is that it includes all types of vulvar SILs, it provides a solution to the concerns in relation to the application of LAST to vulvar lesion, and it is in accordance with the World Health Organization classification as well as the LAST, creating unity among clinicians and pathologists. Abstract : The 2015 ISSVD terminology of vulvar squamous intraepithelial lesions resolves concerns raised with regard to application of the Lower Anogenital Squamous Terminology to vulvar lesions.